1996
DOI: 10.1093/bja/76.5.632
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative inhibition of angiotensin-converting enzyme improves systemic and renal haemodynamic changes during aortic abdominal surgery

Abstract: SummaryWe studied 22 patients undergoing aortic surgery, allocated randomly to receive, before induction of anaesthesia, a single i.v. dose of enalapril 50 g kg 91 or saline. During infrarenal aortic crossclamping, we observed similar reductions in oxygen uptake in the two groups, despite greater systemic oxygen delivery in enalapril-treated patients; angiotensin-converting enzyme inhibition prevented the reduction in cardiac output and attenuated the decrease in glomerular filtration. Changes in glomerular fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Colson et al (31) and Licker et al (32) showed that creatinine clearance was maintained among patients who received an acute administration of ACEI before surgery compared with those receiving placebo. However, the effect of ACEI on kidney function may be different in patients who have been exposed to long-term ACEI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Colson et al (31) and Licker et al (32) showed that creatinine clearance was maintained among patients who received an acute administration of ACEI before surgery compared with those receiving placebo. However, the effect of ACEI on kidney function may be different in patients who have been exposed to long-term ACEI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, use of ACEI during surgery may be beneficial as it attenuates the adrenergic response to stressful stimuli in cardiac surgical patients [1], in vascular surgery patients [3], in those undergoing cerebrovascular surgeries [4], and in patients with impaired LV function [16]. In a recent study of 149 ambulatory surgical patients, Griffin et al [17] showed that discontinuation of ACEI treatment more than 10 hours versus less than 10 hours prior to surgery did not cause an increase in prevalence of preoperative hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative administration of angiotensin-converting enzyme inhibitors (ACEIs) may be beneficial as they attenuate the adrenergic response to stressful stimuli in a variety of patients undergoing cardiac [1], gynecological [2], vascular [3], and cerebrovascular [4] surgeries and in patients with impaired left ventricular (LV) function [4]. Patients taking ACEIs may require more vasopressors to maintain adequate blood pressure (BP) [5,6], and are reportedly at special risk of intraoperative hypotension, especially after anesthetic induction [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…26 Moreover, patients undergoing abdominal aorta surgery pretreated with a single dose of enalapril before anesthesia induction had a significantly greater creatinine clearance on the first postoperative day compared with the placebo group. 27 In a large sample comprising 240,978 patients who underwent inpatient surgery, the authors found that nonresumption of ACEi was independently associated with increased 30-day mortality compared to the restarted group. 28 Our findings in this study also favor the restarting RASi after surgery since PostRASi even provided stronger evidence and longer protection against mortality compared with PreRASi.…”
Section: Discussionmentioning
confidence: 98%